2019
DOI: 10.1142/s0218195919500109
|View full text |Cite
|
Sign up to set email alerts
|

Convex Quadrangulations of Bichromatic Point Sets

Abstract: We consider quadrangulations of red and blue points in the plane where each face is convex and no edge connects two points of the same color. In particular, we show that the following problem is NP-hard: Given a finite set [Formula: see text] of points with each point either red or blue, does there exist a convex quadrangulation of [Formula: see text] in such a way that the predefined colors give a valid vertex 2-coloring of the quadrangulation? We consider this as a step towards solving the corresponding long… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 14 publications
0
2
0
Order By: Relevance
“…In computational geometry, it has been shown that counting the vertices or facets of highdimensional convex polytopes is #P-complete [28], and that computing the expected total length of the minimum spanning tree of a stochastic subset of three-dimensional points is #Phard [25]. Additionally, when testing existence of a geometric structure is hard [5,9,31,29,26] it is just hard to determine whether its count is nonzero. However, we know of no past hardness proofs for counting easy-to-construct two-dimensional structures.…”
Section: Introductionmentioning
confidence: 99%
“…In computational geometry, it has been shown that counting the vertices or facets of highdimensional convex polytopes is #P-complete [28], and that computing the expected total length of the minimum spanning tree of a stochastic subset of three-dimensional points is #Phard [25]. Additionally, when testing existence of a geometric structure is hard [5,9,31,29,26] it is just hard to determine whether its count is nonzero. However, we know of no past hardness proofs for counting easy-to-construct two-dimensional structures.…”
Section: Introductionmentioning
confidence: 99%
“…In computational geometry, it has been shown that counting the vertices or facets of highdimensional convex polytopes is #P-complete [27], and that computing the expected total length of the minimum spanning tree of a stochastic subset of three-dimensional points is #Phard [24]. Additionally, when testing existence of a geometric structure is hard [5,9,25,28,30] it is just hard to determine whether its count is nonzero. However, we know of no past hardness proofs for counting easy-to-construct two-dimensional structures.…”
Section: Introductionmentioning
confidence: 99%